2020
DOI: 10.1016/j.gene.2020.144400
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations and haplotypic diversity in the Myostatin gene of New Zealand cattle breeds

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…All seven of the nucleotide substitutions identified in this study have been previously reported in a study of NZ cattle breeds, which included; Hereford, Angus, Shorthorn, Charolais, Red Poll, South Devon, Simmental, Murray Grey, HF × J cross cattle, and some composite breeds [19]. The nucleotide substitutions c.373+751G/T, c.373+803T/G, c.373+877A/G, c.373+895G/C, and c.374−909C/T were identified in all the ten aforementioned breeds, while c.374−842G/C was found in all but four breeds (Red Poll, Shorthorn, Simmental, and Composites breeds) and the c.374−812A/G was only found in Shorthorn and HF × J cross breeds.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…All seven of the nucleotide substitutions identified in this study have been previously reported in a study of NZ cattle breeds, which included; Hereford, Angus, Shorthorn, Charolais, Red Poll, South Devon, Simmental, Murray Grey, HF × J cross cattle, and some composite breeds [19]. The nucleotide substitutions c.373+751G/T, c.373+803T/G, c.373+877A/G, c.373+895G/C, and c.374−909C/T were identified in all the ten aforementioned breeds, while c.374−842G/C was found in all but four breeds (Red Poll, Shorthorn, Simmental, and Composites breeds) and the c.374−812A/G was only found in Shorthorn and HF × J cross breeds.…”
Section: Discussionsupporting
confidence: 54%
“…The PCR-SSCP analyses coupled with DNA sequencing revealed five banding patterns (A-E) in the region of intron 1 investigated (Figure 1). A total of seven single-nucleotide substitutions (c.373+751G/T, c.373+803T/G, c.373+877A/G, c.373+895G/C, c.374−909C/T, c.374−842G/C, c.374−812A/G) were identified, all of which have been previously reported [19].…”
Section: Identification Of Nucleotide Sequence Variation In Bovine Mstnmentioning
confidence: 56%
See 1 more Smart Citation
“…Unfortunately, the primers used in this study did not cover these loci. Haruna et al [14] found seven nucleotide variations (c.373+751G>T, c.373+803 T>G, c.373+877A>G, c.373+895G>C, c.374-909C>T, c.374-842G>C, c.374-812A>G) in intron 1 of MSTN in New Zealand cattle breeds, of which two variants (c.748-281C>G and c.748-352C>T) have been reported in Qinchuan and Red Angus cattle [11]. In contrast to the results of this study, Haruna et al [14] did not observe any nucleotide variation in exon 1 of the MSTN gene in New Zealand cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the MSTN gene can affect the proper regulation of skeletal muscle mass, which is important for improved meat production traits. Many previous studies have investigated genetic variations of the MSTN gene not only in cattle [3,6,[10][11][12][13][14], but also in other livestock species, including goats [15], geese [16], chickens [17], and sheep [18]. Several cattle breeds are characterized by a double-muscling (DBM) phenotype, which increases muscle mass due to loss-of-function mutations in bovine MSTN [3,10,19,20].…”
Section: Introductionmentioning
confidence: 99%